An Integrated Psycho-Sociological Perspective on Public Employees’ Motivation and Performance - Ciobanu, Alina; Androniceanu, Armenia; Lazaroiu, George (Frontiers in Psychology, 2019)
In the context of profound social, economic and financial changes, private and public organizations managers turn their attention towards the most valuable resource they have – the human resource, the one that can ensure increased organizational performance. Using adequate human resource (HR) policies and practices, organizations can build a positive work environment that sustains employees’ development, encourages communication, innovation and pro-active attitudes and behaviors. However, managerial practices specific to the private sector do not seem to be the solution to the problems public institutions deal with. While specialists have mainly explored the link between human resources management (HRM) and performance in the private sector, due consideration ought to be paid to the particularities of this relationship in the public sector as well, and to the factors that influence public employees’ motivation and determine their level of performance. The purpose of our paper is to show that HRM in public institutions should be approached in a manner that focuses more on the work motivation theory, specifically on the psycho-sociological profile of the public employee, and argue that higher performance can be achieved by establishing a social exchange relationship between managers and the members of their teams. A supportive work environment positively impacts upon public employees’ performance, self-efficacy and job satisfaction, even though they are mainly driven in performing their tasks by intrinsic motivators and devotion to public values and interest.